Implementasi Program Bina Pribadi Islam (BPI) dalam Mengatasi Perilaku Cyberbullying Pada Siswa SMP IT Al Hijrah - Anju Yurika Pasaribu; Mardianto Mardianto (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the implementation of the Islamic Personal Development Program (BPI) in overcoming cyberbullying behavior in students of SMP IT Al Hijrah, with a focus on the formation of a holistic Islamic character. This study uses a qualitative method with a case study approach. Data were collected through observation of the BPI activity process, interviews with BPI supervisors, homeroom teachers, students, and supporting documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the Islamic Personal Development Program (BPI) is able to shape the character of students well, through BPI programs such as congregational prayer, dhuha prayer, tahajud, fasting, charity, Jalasi Ruhi, heart check, mabit, from these activities that give birth to character and cyberbullying behavior in students of SMP IT Al Hijrah can be overcome. However, the success of this BPI program must have cooperation between the school and parents.